Impacto da espécie invasora Ceratium furcoides (levander) langhans 1925 em duas represas do Alto Jacuí, RS - Cassol, Ana Paula Vestena (2014)
Species of the dinoflagellate genus Ceratium are preferentially marine, and their presence in tropical and subtropical freshwater systems has been considered invasive. The first record of its presence in Brazil was published in 2006 for São Paulo state. Since then, the species has been reported from several different river systems, sometimes in high densities characterizing blooms. The study described herein aimed at identifying the impacts of the occurrence in high densities of the species Ceratium furcoides and its possible relationships with other phytoplankton species at two reservoirs, Ernestina and Itaúba, located in the high course of the river Jacuí, Rio Grande do Sul state, Brazil. Another aim was to describe spatial and seasonal patterns of the phytoplankton community, related to limnological and climatological variables, in order to illustrate the regulating processes of these communities. Samplings were taken seasonally from January 2012 to January 2013. Ernestina reservoir is the first lake of the cascade system with an area of 38.5 km2 and 7.1m average depth. Itaúba is the fourth dam, with 13.2km2 area and average depth of 40m. Samples were taken from four sampling stations in each reservoir and three depths using a five litre Van Dorn bottle and filtering the content through a 10 μm mesh plankton net. After microscopic analysis of lugol preserved samples, 91 species were identified from Ernestina and 130 from Itaúba. The communities were organized seasonally. There were no significant differences in spatial patterns (vertical or horizontal). Species richness increased with higher rainfall and cell densities were higher at longer hydraulic retention times, mostly noticeable in the Itaúba lake. Mixing and stratification of water layers related to morphometric characteristics of the reservoirs were important regulators of phytoplankton in both lakes. The first record of C. furcoides was for January 2012 in Itaúba and May 2012 in Ernestina, and it was present in every subsequent sample of both reservoirs. Densities of C. furcoides higher than 100 cel mL-1 were found in samples with 20°C average temperature and basic pH in Itaúba. Low phosphate levels were not limiting for the development of the species and higher rainfall caused a decrease in cell numbers. Other species occurring in Itaúba while the dinoflagellate was in bloom were Eudorina sp, Cyclotella meneghiniana, Discostella stelligera, and Cuspidotrhix. There was a marked decrease in species richness while the highest biovolume of C. furcoides was found in Itaúba. The first record of C. furcoides blooming in the reservoirs of the high course of the river Jacuí suggests a modification in local environmental conditions, reinforcing the need for a better understanding of the consequences of such blooms for the system.